Contribution of TEX15 genetic variants to the risk of developing severe non-obstructive oligozoospermia - Guzmán-Jiménez, Andrea; González-Muñoz, Sara; Cerván-Martín, Miriam; Rivera-Egea, Rocío; Garrido, Nicolás; Luján, Saturnino; Santos-Ribeiro, Samuel; Castilla, José A.; Gonzalvo, M. Carmen; Clavero, Ana; Vicente, F. Javier; Maldonado, Vicente; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: Severe spermatogenic failure (SPGF) represents one of the most relevant causes of male infertility. This pathological condition can lead to extreme abnormalities in the seminal sperm count, such as severe oligozoospermia (SO) or non-obstructive azoospermia (NOA). Most cases of SPGF have an unknown aetiology, and it is known that this idiopathic form of male infertility represents a complex condition. In this study, we aimed to evaluate whether common genetic variation in TEX15, which encodes a key player in spermatogenesis, is involved in the susceptibility to idiopathic SPGF. Materials and Methods: We designed a genetic association study comprising a total of 727 SPGF cases (including 527 NOA and 200 SO) and 1,058 unaffected men from the Iberian Peninsula. Following a tagging strategy, three tag single-nucleotide polymorphisms (SNPs) of TEX15 (rs1362912, rs323342, and rs323346) were selected for genotyping using TaqMan probes. Case-control association tests were then performed by logistic regression models. In silico analyses were also carried out to shed light into the putative functional implications of the studied variants. Results: A significant increase in TEX15-rs1362912 minor allele frequency (MAF) was observed in the group of SO patients (MAF=0.0842) compared to either the control cohort (MAF=0.0468, OR=1.90, P=7.47E-03) or the NOA group (MAF=0.0472, OR=1.83, P=1.23E-02). The genotype distribution of the SO population was also different from those of both control (P=1.14E-02) and NOA groups (P=4.33-02). The analysis of functional annotations of the human genome suggested that the effect of the SO-associated TEX15 variants is likely exerted by alteration of the binding affinity of crucial transcription factors for spermatogenesis. Conclusion: Our results suggest that common variation in TEX15 is involved in the genetic predisposition to SO, thus supporting the notion of idiopathic SPGF as a complex trait.